Strategi Promosi Wisata Mangrove Wonorejo Dalam Menarik Wisatawan - Rahmat, Dedy (Universitas Negeri Surabaya, 2022)
Wonorejo Mangrove ecotourism is one of the largest ecotourism locations in East Java, Surabaya. The Wonorejo Mangrove since 2008 has been transformed into a tourist destination that provides education to the public about the importance of the environment, but because the location in Surabaya is only known by its name but not by its place and destination, this is because the name Surabaya is attached as a metropolitan city, trade, and transit. goods between provinces. So it is necessary to do a promotion strategy for mangrove tourism in Wonorejo. The research method used in this study is a qualitative approach where this approach tries to understand the phenomenon in its natural setting and context, where the researcher does not manipulate the observed phenomena, then analyzes the data using qualitative descriptive and triangulation. The concept of tourism promotion uses the AISAS concept, namely Attention, Interest, Search, Action, and Share. The tourism promotion strategy was developed through holding events, exhibitions, distributing brochures and promotions through social media. Key Words: Mangroves, Ecotourism, Strategy, Promotion